Cephalopod‐Inspired Stretchable Self‐Morphing Skin Via Embedded Printing and Twisted Spiral Artificial Muscles. (13th September 2021) - Fei, Fan; Kotak, Parth; He, Li; Li, Xiaofeng; Vanderhoef, Cyan; Lamuta, Caterina; Song, Xuan
Abstract: Cutaneous muscles drive the texture‐modulation behavior of cephalopods by protruding several millimeters out of the skin. Inspired by cephalopods, a self‐morphing, stretchable smart skin containing embedded‐printed electrodes and actuated by Twisted Spiral Artificial Muscles (TSAMs) is proposed. Electrothermally actuated TSAMs are manufactured from inexpensive polymer fibers to mimic the papillae muscles of cephalopods. These spirals can produce strains of nearly 2000% using a voltage of only 0.02 V mm −1 . Stretchable and low‐resistance liquid metal electrodes are embedded‐printed inside the self‐morphing skin to facilitate the electrothermal actuation of TSAMs. Theoretical and numerical models are proposed to describe the embedded printing of low‐viscosity Newtonian liquid metals as conductive electrodes in a soft elastomeric substrate. Experimental mechanical tests are performed to demonstrate the robustness and electrical stability of the electrodes. Two smart skin prototypes are fabricated to highlight the capabilities of the proposed self‐morphing system, including a texture‐modulating wearable soft glove and a waterproof skin that emulates the texture‐modulation behavior of octopi underwater. The proposed self‐morphing stretchable smart skin can find use in a wide range of applications, such as refreshable Braille displays, haptic feedback devices, turbulence tripping, and antifouling devices for underwater vehicles. Abstract : Inspired by cephalopods, a self‐morphing, stretchable smart skin containing embedded‐printed electrodes and actuated by twisted spiral artificial muscles is developed. The proposed self‐morphing stretchable smart skin can find use in a wide range of applications, such as refreshable Braille displays, haptic feedback devices, turbulence tripping, and antifouling devices for underwater vehicles.